2007
DOI: 10.1016/j.carbon.2006.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Binding of pulmonary surfactant proteins to carbon nanotubes; potential for damage to lung immune defense mechanisms

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 28 publications
(45 reference statements)
7
66
0
1
Order By: Relevance
“…As pBALF is not Ca 2+ -free, an ion-mediated adsorption to the organic groups of the two particles via the CRD domain of SP-A may be possible, similarly as has been suspected by Salvador-Morales and Co-workers for accidental organic modifications of carbon nanotubes [28]. black is nearly total, the possibility of not only protein-particle, but also protein-protein interaction is given.…”
Section: Particle Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…As pBALF is not Ca 2+ -free, an ion-mediated adsorption to the organic groups of the two particles via the CRD domain of SP-A may be possible, similarly as has been suspected by Salvador-Morales and Co-workers for accidental organic modifications of carbon nanotubes [28]. black is nearly total, the possibility of not only protein-particle, but also protein-protein interaction is given.…”
Section: Particle Propertiesmentioning
confidence: 85%
“…A major biological role of SP-A is to bind to inhaled particulate matter (e.g. microorganisms, dust, etc) to enhance their phagocytic clearance by macrophages [28,48,49]. In this way, SP-A plays an important role in limiting pulmonary infection, lung allergy and inflammation [50].…”
Section: Investigation Of Deagglomeration Capacity Of Pbalfmentioning
confidence: 99%
“…53 It has also been demonstrated that chronic exposure to CNTs results in a sequestration of surfactant proteins A and D ͑SP-A and SP-D͒ and collectins, which are known to play a relevant defensive role against infections within the lung. 54 As a consequence, a relevant reduction in immune defense is induced due to both macrophages impairment and direct binding of surfactant proteins. The extent of these effects is likely to be driven by morphology and dimensions of CNTs.…”
Section: Biological Bases Of Cnt Toxicitymentioning
confidence: 99%
“…For example, CNTs could bind with pulmonary surfactant proteins A and D and then lead to susceptibility of lung infection and emphysema in mice (29). When the functionalized CNTs were bound to the α-chymotrypsin, the complex could inhibit enzymatic activity (30).…”
mentioning
confidence: 99%